Association between circulating exhausted CD4+ T cells with poor meningococcal C conjugate vaccine antibody response in HIV-infected children and adolescents - Silva, Giselle P.; Pereira-Manfro, Wania F.; Costa, Priscilla R.; Costa, Dayane A.; Ferreira, Bianca; Barreto, Daniela M.; Frota, Ana Cristina C.; Hofer, Cristina B.; Figueredo, Carlos M.; Coelho, Barbara; Kallas, Esper G.; Milagres, Lucimar G. (Clinics, 2021)
OBJECTIVES: To investigate the expression levels of surface markers of activation (CD38 and HLA-DR), inhibition (PD-1, TIGIT and CD57) and co-stimulation (CD28 and CD127) on CD4+ T cells of children/adolescents with vertical HIV infection (HI patients) and HIV-uninfected (HU) controls vaccinated with the meningococcal C conjugate vaccine (MCC). METHODS: HI patients (n=12), aged 8–17 years, were immunized with two MCC injections, while HU controls (n=9), aged 5.3–10.7 years, received a single MCC dose (as per national recommendation at the time of this study, a single MCC vaccine dose should be given for healthy children and youth aged 1–18 years). The HI patients were categorized according to the combined antiretroviral therapy (cART) treatment. Blood samples were obtained before vaccination, after priming, and after the administration of a booster dose of vaccine to determine the serum bactericidal antibody (SBA) titers and the expression levels of surface markers on CD4+ T cells by flow cytometry. The levels of serum cytokines, IL-4 and CXCL-13 were also measured using Luminex kits. RESULTS: The co-expression of the TIGIT-HLA-DR-CD38 molecules increased in the CD4+ T cells of HI patients/ no-cART who also showed a lower frequency of CD127+CD28+ CD4+ T cells than HI patients/cART and HU group subjects. There were significant negative correlations between the frequency of exhausted CD4+ T cells and the SBA response. IL-4 levels were higher in HI patients/cART and positively correlated with SBA titers but negatively associated with the expression of exhaustion markers. Moreover, the CXCL-13 levels were positively correlated with the exhausted CD4+ T cells. CONCLUSION: The results of our study suggest that the co-expression of exhaustion markers and/or loss of co-stimulatory molecules influence the SBA response in HI patients.